Smoothlink: Towards a Web-based Media Context Migration Environment - Serrano, U.; Osmani, F.; Knutsson, B. (2012 IEEE 10th International Symposium on Parallel and Distributed Processing with Applications, 2012)
Current migration mechanisms for multimedia content in ubiquitous environments lack simplicity and wide deployment across user personal devices. To address this concern, we focus on prospects of wider adoption by designing and implementing a mechanism that enables the user to easily migrate media context between her Internet-enabled devices, regardless of the networks they access. Our proposed architecture employs open web standards while highly prioritizing modularity and sketches a path to increase device compatibility.